Update on pharmacotherapy for pulmonary hypertension. Issue 6 (19th September 2016) - Prior, David L; Adams, Heath; Williams, Trevor J
Summary: Pulmonary arterial hypertension (PAH) is a rare disease with a poor prognosis if not treated. Pharmacological treatment options for PAH have increased significantly over the past 10 years, with availability of intravenous, oral and inhaled drugs targeting the nitric oxide, endothelin and prostacyclin pathways. Treatment with these therapies in specialised pulmonary hypertension centres has resulted in reductions in patient symptoms, disease progression and mortality, and improved exercise capacity. Recognition of chronic thromboembolic pulmonary hypertension is important, as this cause of pulmonary hypertension may be amenable to surgical treatment. Several new oral drugs, including macitentan, riociguat and selexipag, some of which have novel modes of action, and the use of combinations of PAH drugs have recently been shown to be beneficial in treating PAH and are likely to change treatment for this condition in the future.